High performance and small footprint spot size converters based on SWG metamaterial lenses - Luque-González, José Manuel; Molina-Fernández, Íñigo; Ortega-Moñux, Alejandro; Halir, Robert; Schmid, Jens H.; Cheben, Pavel (My University, 2018)
Spot size converters with high expansion ratio are required in a variety of situations. This is the case of non-focusing Silicon on Insulator (SOI) fiber-to-chip grating couplers, which typically require long adiabatic tapers (Ltaper >100μm) from the narrow single-mode waveguides (WSi-wire ~ 500nm) to the wide grating region (Wgrating ~ 15μm). Here, we explore the potential of subwavelength grating (SWG) dielectric metamaterials to implement integrated GRaded INdex (GRIN) lenses to expand the mode field. Our designs achieve the desired Beam Expansion (BE) with insertion losses below 1dB over a distance of only LBE ~ 17μm.
Keywords: Microelectrónica - Congresos; Subwavelength grating; Graded index; Beam expander; Silicon-On-Insulator; Grating coupler